2014
DOI: 10.1371/journal.pone.0088726
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazoisoquinolines: A New Class of Rapidly Metabolized Aryl Hydrocarbon Receptor (AhR) Ligands that Induce AhR-Dependent Tregs and Prevent Murine Graft-Versus-Host Disease

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that plays multiple roles in regulation of immune and inflammatory responses. The ability of certain AhR ligands to induce regulatory T cells (Tregs) has generated interest in developing AhR ligands for therapeutic treatment of immune-mediated diseases. To this end, we designed a screen for novel Treg-inducing compounds based on our understanding of the mechanisms of Treg induction by the well-characterized immunosuppressive AhR lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 44 publications
2
55
1
3
Order By: Relevance
“…The dose of 10-Cl-BBQ was calculated empirically by determining a concentration that would induce equivalent Cyp1a1 expression as a body burden of 25 μg/kg TCDD, the therapeutic dose in NOD mice. Because NOD mice express the low responder AhR d allele, they require a higher dose of 10-Cl-BBQ to achieve comparable activation of AhR when compared to AhR b expressing C57BL/6 mice (13). Oral treatment with 60 mg/kg 10-Cl-BBQ induced commensurate expression of Cyp1a1 as the therapeutic dose of TCDD in NOD mice (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dose of 10-Cl-BBQ was calculated empirically by determining a concentration that would induce equivalent Cyp1a1 expression as a body burden of 25 μg/kg TCDD, the therapeutic dose in NOD mice. Because NOD mice express the low responder AhR d allele, they require a higher dose of 10-Cl-BBQ to achieve comparable activation of AhR when compared to AhR b expressing C57BL/6 mice (13). Oral treatment with 60 mg/kg 10-Cl-BBQ induced commensurate expression of Cyp1a1 as the therapeutic dose of TCDD in NOD mice (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the notoriety of TCDD as an environmental toxicant would likely limit its acceptance for pharmacologic uses. To identify other high-affinity AhR ligands that exhibit more favorable pharmacokinetic properties than TCDD, we used small-molecule screening to discover a novel immunosuppressive AhR ligand, 10-Cl-BBQ (13). This nontoxic compound was shown to have an in vivo half-life of approximately two hours but could be administered to mice in a repeated dosing scheme to maintain AhR activation over time, similar to the prolonged AhR activation induced by TCDD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, in this study, a novel water-soluble derivative of the compound VAF347 (VAG539) was found to promote longterm graft acceptance and active tolerance in BALB/c mice that received a transplant of MHC-mismatched pancreatic islet allografts. Also in the search for novel potential AhR-activating molecules to be used in transplantation tolerance, Punj et al screened a ChemBridge small molecule library (ChemBridge Corp, San Diego, CA) and identified 10-chloro-7H-benzimidazo[2,1-a]benzo[de]isoquinolin-7-one (10-Cl-BBQ) as a novel potent AhR ligand (30). They found that daily treatments with 10-Cl-BBQ during the GVHD response resulted in increased expression of several genes associated with Treg function and prevented the development of GVHD in an AhR-dependent manner.…”
Section: Outcomes Of Ahr Activation In Transplantation Immunitymentioning
confidence: 99%
“…[19][20][21] To examine whether AhR participates in the induction of SIN on Treg cells, the potential cytotoxicity of SIN in EL-4 cells was tested and the optimal concentrations (0.1, 0.3, and 1 mM) were used in the following studies, whereas TCDD was used as a positive control. SIN induced the expression of CYP1A1 (target gene of AhR) at protein and mRNA levels in a concentration-dependent manner, and it also markedly promoted the CYP1A1 activity (Figures 3a-c).…”
Section: Sin Induced the Expression Of Cyp1a1 In Lymphocytes Dependenmentioning
confidence: 99%